2019
DOI: 10.1182/bloodadvances.2018028522
|View full text |Cite
|
Sign up to set email alerts
|

KDM2B in polycomb repressive complex 1.1 functions as a tumor suppressor in the initiation of T-cell leukemogenesis

Abstract: KDM2B together with RING1B, PCGF1, and BCOR or BCORL1 comprise polycomb repressive complex 1.1 (PRC1.1), a noncanonical PRC1 that catalyzes H2AK119ub1. It binds to nonmethylated CpG islands through its zinc finger-CxxC DNA binding domain and recruits the complex to target gene loci. Recent studies identified the loss of function mutations in the PRC1.1 gene, BCOR and BCORL1 in human T-cell acute lymphoblastic leukemia (T-ALL). We previously reported that Bcor insufficiency induces T-ALL in mice, supporting a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
(59 reference statements)
0
20
0
Order By: Relevance
“…In addition, ChIP with IgG was used as a negative control to determine the background level of ChIPs while an intergenic region on the host genome (Neg) was used as an additional negative control for the ChIP assays. As a positive control for the KDM2B ChIP we used Myc promoter where KDM2B is known to bind (Fig 8D) [46]. Our results showed that the enrichment of KDM2B on the RTA promoter was gradually increased along with RYBP while the ChIP signal in the IgG ChIP samples and on the Neg region remained low indicating the specificity of KDM2B and RYBP ChIPs (Fig 8A).…”
Section: Kdm2b Rapidly Binds To the Kshv Genome During De Novo Infectmentioning
confidence: 86%
“…In addition, ChIP with IgG was used as a negative control to determine the background level of ChIPs while an intergenic region on the host genome (Neg) was used as an additional negative control for the ChIP assays. As a positive control for the KDM2B ChIP we used Myc promoter where KDM2B is known to bind (Fig 8D) [46]. Our results showed that the enrichment of KDM2B on the RTA promoter was gradually increased along with RYBP while the ChIP signal in the IgG ChIP samples and on the Neg region remained low indicating the specificity of KDM2B and RYBP ChIPs (Fig 8A).…”
Section: Kdm2b Rapidly Binds To the Kshv Genome During De Novo Infectmentioning
confidence: 86%
“…For example, the PRC1.1 complex is also important in preventing T-cell acute lymphoblastic leukemia (T-ALL). Mice lacking the PUFD domain of BCOR (same floxed allele as present study) or the zinc finger domain of KDM2B both developed lethal T-ALL (Tara et al 2018;Isshiki et al 2019), suggesting a broader role for PRC1.1 as a tumor suppressor in cancer.…”
Section: Bcor Directly Represses Igf2 Via Prc11 Complex-mediated H2amentioning
confidence: 58%
“…23,24 Recent research has indicated that polycomb group members, such as EZH2, Bmi1, KDM2B, PHF19, SUZ12, CBX8, and so on, are involved in the proliferation of cancer cell including glioma cells. 20,[25][26][27][28][29][30][31] In the present study, we revealed the association between PCGF1 and various characteristics of glioblastoma (GBM).…”
Section: Discussionmentioning
confidence: 73%